Rescue PCI in the management of STEMI: Contemporary results from the Melbourne Interventional Group registry() - Fernando, Himawan (Int J Cardiol Heart Vasc, 2021)
BACKGROUND: Fibrinolysis is an important reperfusion strategy in the management of ST-elevation myocardial infarction (STEMI) when timely access to primary percutaneous coronary intervention (PPCI) is unavailable. Rescue PCI is generally thought to have worse outcomes than PPCI in STEMI. We aimed to determine short- and long-term outcomes of patients with rescue PCI versus PPCI for treatment of STEMI. METHODS AND RESULTS: Patients admitted with STEMI (excluding out-of-hospital cardiac arrest) within the Melbourne Interventional Group (MIG) registry between 2005 and 2018 treated with either rescue PCI or PPCI were included in this retrospective cohort analysis. Comparison of 30-day major adverse cardiac events (MACE) and long-term mortality between the two groups was performed. There were 558 patients (7.1%) with rescue PCI and 7271 with PPCI. 30-day all-cause mortality (rescue PCI 6% vs. PPCI 5%, p = 0.47) and MACE (rescue PCI 10.3% vs. PPCI 8.9%, p = 0.26) rates were similar between the two groups. Rates of in-hospital major bleeding (rescue PCI 6% vs. PPCI 3.4%, p = 0.002) and 30-day stroke (rescue PCI 2.2% vs. PPCI 0.8%, p < 0.001) were higher following rescue PCI. The odds ratio for haemorrhagic stroke in the rescue PCI group was 10.3. Long-term mortality was not significantly different between the groups (rescue PCI 20% vs. PPCI 19%, p = 0.33). CONCLUSIONS: With contemporary interventional techniques and medical therapy, rescue PCI remains a valuable strategy for treating patients with failed fibrinolysis where PPCI is unavailable and it has been suggested in extenuating circumstances where alternative revascularisation strategies are considered.